The Effects of Fluidized Bed Drying, Soaking, and Microwaving on the Phytic Acid Content, Protein Structure, and Digestibility of Dehulled Faba Beans - Cheng, Shu (2023)
Different pre-treatments of pulses affect the content of antinutritional factors and protein digestibility. This study addresses the challenge of removing phytic acid, which is one of the major anti-nutritional factors present in faba beans. From this study, fluidized bed drying at 120 ◦C and 140 ◦C removed 8–22% of the phytic acid present. Phytic acid is thermally stable, and drying did not lead to a large reduction in concentration. Greater drying temperatures and drying times had little effect on the removal of phytic acid. Soaking the dehulled faba beans in 0.1% citric acid for 12 h at 37 ◦C removed 51 ± 11% of the phytic acid. After soaking for 12 h, microwaving the faba beans for two minutes removed over 70% of the phytic acid, including soaking in water or soaking in 0.1% citric acid solution. The mechanism for phytic acid reduction after microwaving appears to be linked with changes in the cotyledon cellular structure of the faba bean, as demonstrated using scanning electron microscopy. The protein secondary structure in the faba bean was modified after microwaving. The in vitro protein digestibility of dehulled faba beans used in this study increased by 15.7% compared with the fresh faba beans of 75.5 ± 0.5%. The in vitro digestibility of dehulled faba beans increased to 88.3 ± 0.6% after two minutes of microwaving, so both dehulling and microwaving improved the digestibility of the faba bean proteins.